PERANCANGAN GEDUNG GEREJA KATOLIK DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR DI SAMARINDA - vito, wirawan ivan (Jurnal Totem : Architecture, Environment, Region and Local Wisdom, 2021)
The research objective of designing a catholic church building in the city of Samarinda is as a facility that can accommodate worship activities and fostering Catholics with a neo vernacular architectural approach. The benefits of research are to provide knowledge and insight regarding the design of worship facilities and guidance, especially for Catholics with a neo vernacular architectural approach. Primary data research methodology direct interviews with relevant sources to get solid information. Observation, namely by making direct observations in the field. Secondary data searches literature related to church building design in books / internet. The results of this research are determining the concept of building design and the achievement of the design of a catholic church building with a neo vernacular architectural approach in Samarinda.